SOCIAL ADAPTATION AND GENDER BALANCE IN MILITARY FAMILIES: THEORETICAL AND PRACTICAL ASPECTS (Universal International Scientific Journal, 2026)
This thesis analyzes the role of family psychology in the formation of moral and ethical immunity in modern conditions of increased information attacks and the impact of gender stereotypes on child upbringing. The study highlights the impact of the psychological environment in the family, parental upbringing styles, and social views on the personal development of a child. The results show that a healthy family environment and upbringing based on the principles of equality increase the resilience of the younger generation to information attacks.
Keywords: military families; information attacks; moral immunity